Pengaruh Kualitas Pelayanan Terhadap Keputusan Memilih Hotel dan Wisma di Kabupaten Pinrang - Suardi (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2020)
This research is to find out and analyze the quality of service consisting of physical evidence, empathy, responsiveness, reliability and guarantee influence on the decision to choose a hotel and guesthouse in Pinrang Regency. To find out and analyze which quality of service is dominant which influences the decision to choose a hotel and guesthouse in Pinrang Regency. The study was conducted in Pinrang Regency with a population of 385 hotel/guesthouse/inn customers and determined a sample of 196 respondents based on the Slovin formula. Data from the questionnaire were analyzed using descriptive analysis and Multiple Linear Regression. The results of the study found that the quality of service consisting of physical evidence, empathy, responsiveness, reliability and guarantee influence the decision to choose a hotel and guesthouse in Pinrang Regency. The results of multiple linear regression analysis show that physical evidence, empathy and reliability have a positive and significant influence on customer choice decisions, while responsiveness and guarantees have a negative and not significant effect on customer choice decisions. This means that the decision to choose a hotel and a guesthouse is determined by the existence of physical evidence from a hotel or guesthouse that gives comfort to each hotel guest, shows an attitude of care (empathy) in serving hotel guests and the reliability of its employees who provide a fast and non-discriminatory service process.